Investigating the relationship between quality of primary care and premature mortality in England: a spatial whole-population study. (2nd March 2015) - Kontopantelis, Evangelos; Springate, David A; Ashworth, Mark; Webb, Roger T; Buchan, Iain E; Doran, Tim
Abstract : Objectives To quantify the relationship between a national primary care pay-for-performance programme, the UK's Quality and Outcomes Framework (QOF), and all-cause and cause-specific premature mortality linked closely with conditions included in the framework. Design Longitudinal spatial study, at the level of the "lower layer super output area" (LSOA). Setting 32482 LSOAs (neighbourhoods of 1500 people on average), covering the whole population of England (approximately 53.5 million), from 2007 to 2012. Participants 8647 English general practices participating in the QOF for at least one year of the study period, including over 99% of patients registered with primary care. Intervention National pay-for-performance programme incentivising performance on over 100 quality-of-care indicators. Main outcome measures All-cause and cause-specific mortality rates for six chronic conditions: diabetes, heart failure, hypertension, ischaemic heart disease, stroke, and chronic kidney disease. We used multiple linear regressions to investigate the relationship between spatially estimated recorded quality of care and mortality. Results All-cause and cause-specific mortality rates declined over the study period. Higher mortality was associated with greater area deprivation, urban location, and higher proportion of a non-white population. In general, there was no significant relationship between practice performance on quality indicators included in the QOF and all-cause or cause-specific mortality rates in the practice locality. Conclusions Higher reported achievement of activities incentivised under a major, nationwide pay-for-performance programme did not seem to result in reduced incidence of premature death in the population.